Mineral Supertrumps: A New Card Game to Assist Learning of Mineralogy. Issue 2 (1st May 2016) - Spandler, Carl
ABSTRACT: Mineralogy is an essential component of Earth Science education, yet many students struggle to obtain adequate comprehension and knowledge of mineralogy during tertiary (postsecondary) degree programs. The use of educational games can be an effective strategy for science teaching as games provide an active learning environment that enhances student engagement and motivation. This paper introduces a new card game called "Mineral Supertrumps" that can be used to counter the challenge of learning mineralogy at either secondary or tertiary level. The card game includes information on the properties of 54 minerals, which include the most important rock-forming minerals as well as minerals of industrial and economic significance. The game is easy to learn and play, and it is designed to motivate learning of mineral properties through active and competitive game-play in a group setting. Group play also helps to build identity and culture around student cohorts, which may also promote learning outcomes. Most students in the second year of a tertiary geology program surveyed after playing the game found it enjoyable to play and considered it to be effective for enhancing learning about mineral properties and their application to society and other Earth Science disciplines. Nevertheless, our survey results also indicate that student engagement with the game (and hence, learning benefits) may be limited if the game is not integrated with other course content, and/or it is not linked to incentive-based exercises (e.g., assessment).